Use of MitraClip system for severe mitral regurgitation in cardiogenic shock: results from a multicentre observational Italian experience (the MITRA-SHOCK study). (25th November 2020) - Falasconi, G; Pannone, L; Melillo, F; Adamo, M; Ronco, F; Carrabba, N; Citro, R; Stella, S; Ingallina, G; Capogrosso, C; Scandroglio, M; Ancona, F; et al.
Abstract: Background/Introduction: Cardiogenic shock (CS) is a medical emergency and a frequent cause of death. CS can be complicated by mitral regurgitation (MR). The presence of at least moderate MR in the setting of shock was associated with about three-times higher odds of 1-year mortality. In the setting of refractory CS, percutaneous mitral valve repair (PMVR) can be a potential therapeutic option. Purpose: The aim of the study was to evaluate the efficacy of percutaneous approach of severe MR in patients with CS assessing short-term clinical outcomes. Methods: In this study we retrospectively included patients with CS and concomitant severe MR treated with Mitraclip system. We enrolled 28 patients from 5 Italian centers between 2012 and 2019. MitraClip implantation was performed according to each hospital standard care. CS was defined utilizing the Diagnostic Criteria of Cardiogenic Shock used in the SHOCK trial. Procedural success was defined as the presence of moderate or less MR after MitraClip implantation. Results: All patients presented at least severe MR. All treated patients were at high surgical risk (STS mortality score 36.4±11.7%). Procedural success was obtained in 24 patients (86%). A mean of 1.71±0.76 clips per patients were implanted. In-hospital complications occurred in 13 patients (46%): 7 minor bleedings (25% of patients), 7 major bleedings (25%), 8 acute kidney injuries (28%). In-hospital mortality was 25% and the reported causes of death were cardiovascular in all patients. At Cox multivariate analysis procedural success was a strong predictor of in-hospital survival (HR 0.11, CI 95% 0.02–0.67, p=0.017). Conclusions: PMVR with Mitraclip system in patients with CS and concomitant MR demonstrated high procedural success and acceptable safety. It can be considered a bailout option in this setting of patients with high short-term mortality. Larger prospective studies are needed. Funding Acknowledgement: Type of funding source: None